A case study on book censorship against book selection standards and library practices of sectarian high school libraries in District IV of Quezon City - Haduca, Fairlyn R.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The primary motivation of this study is based on the issue of book censorship against book selection standards and library practices in the library. Censorship is a complex issue that brought up heated discussions and intense studies. The basic problem with censorship is its extremely close relationship with book selection and library practices. Some believe that book selection may result to book censorship while others believe that both book selection and censorship differ with one another.
This study was conducted to investigate the issue of book censorship against book selection standards and practices in a sectarian high school library setting. This study tried to determine if librarians are acting as censors or mere selectors in their library on the basis of their selection policies and library practices. The study also aimed to observe if other manifestations of censorship such as book labeling, banning, cutting, restricting, prohibiting and rejecting are practiced in sectarian high school libraries.
The study made use of the descriptive method of research. Book censorship in book selection policies and library practices is determined through the review of the libraries' Collection and Development policy, review of the libraries' collection of fiction and interview with the head librarian of the schools. The Collection and Development Policy is scanned to check the standards and policies of the libraries regarding book selection and acquisition. The study noted the collection of the libraries being studied and for that the list of frequently challenged young adult fiction books prepared by ALA found in YALSA's hit List: Frequently Challenged Books for Young Adults and those found in the Internet are consulted. The data gathered from the interview with the head librarian of the schools studied are supplementary yet critical because they provided other important insights.
It was found out that the basic problem lies in the selection policies of the schools. There is lack of specific criteria on the selection policy, or even if there are enough specific criteria, there is not enough implementation of those criteria. There are considerations taken in selection and acquisition of the materials such as budget, the availability and necessity of the materials, the demands of the students, the recommendations of the faculty, and objectives, philosophy, Mission and Vision of the school. The sectarian high school libraries studies have no written policies/standards regarding book censorship. There have been themes that the libraries refrain from acquiring such as pornography and violence. One of the libraries studies is practicing closed-shelving that includes restricting circulation of books for a particular age group. However, the schools do not have a history of book labeling, burning and cutting. From the findings, the researcher found out that censorship does not exist in the policies and standards of the library, but most of the time, it exists in library practices wherein there are implementations that are not based on standards and policies. Thus, inconsistency between library theory and practice occurred that would result in censorship. It is recommended that the schools studied should adapt precise and concrete policies in book selection. Consistency between the library's theory and practice should be observed.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Book selection -- Standards; Censorship; Elementary school libraries -- Book selection -- Philippines -- Quezon City